Linking product differentiation and hybrid innovation to enterprise performance: The mediating role of competitive advantage in the automotive components industry - Dudi, Dudi; Mulyanto, Heru (Institute of Computer Science (IOCS), 2026)
This study aims to analyze the influence of product differentiation and hybrid innovation on the performance of companies with competitive advantages as a mediating variable in the automotive component industry. The phenomenon of declining market share of PT XYZ, Bogor is the background for the urgency of this research. Using a quantitative approach, data was collected through a questionnaire from 100 respondents using a snowball sampling technique. Data analysis was carried out using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method through SmartPLS 4 software. The results of the study show that product differentiation has a significant positive effect on the company's performance directly. In contrast, hybrid innovation does not have a direct effect on performance, but has a significant influence through the mediation of competitive advantage. These findings confirm that competitive advantage serves as a perfect mediator for hybrid innovation in boosting business performance. Practically, the company is advised to strengthen its competitive position through the integration of technology and product added value to achieve sustainable superior performance in the dynamic automotive market.